Beyond the grave - Watson, Jude (New York : Scholastic, 2009)
A Clue found in book 3 sends Amy and Dan jetting off to find out just what's behind the fierce rivalry between the Tomas and Ekaterina branches of the Cahill family. Was a Clue stolen from the Tomas branch? Where is it now? And most important, can Amy and Dan get their hands on it before their rivals do?
Keywords: Code and cipher stories; Detective and mystery fiction